Perfil comunicativo de crianças que ingressaram na educação infantil após os cinco anos de idade - Oliveira, Jáima Pinheiro de [UNESP]; Oliveira, Rudahyra Thaísa Osswald de; Bougo, Graziela Chamarelli; Zaboroski, Ana Paula; Schier, Ana Cândida (My University, 2010)
Objective: To characterize the communicative behaviors of children who entered in Primary School after the age of five. Methods: It was a descriptive study, held in a city at the countryside of Parana state (Brazil), in the years 2007 and 2008, in both school and home environments. Twelve children of both genders joined in the study, with age ranging from five years and two months to six years, besides their mothers and respective teachers. Interviews were conducted with mothers and a questionnaire for teachers. Afterwards, observations of the communication of children in school and home environments were conducted. Data analysis focused on those relevant to children’s development and school performance, trying to determine their communicative profile in school and home environments, from protocols regarding the indicators of communication means and functions. Results: The results indicated the presence of a child with poor general health, with complications from the pregnancy period, with motor and language delays and low school performance. It was also observed that all children used verbal means to communicate and the highest frequency of communicative functions appeared in home environment, indicating an important aspect to be considered in the stimulation of communication of these children. Conclusion: Data from this study showed that the children benefited more of contexts planned with family interlocutors.

Objetivo: Caracterizar os comportamentos comunicativos emitidos por crianças que ingressaram na Educação Infantil após os cinco anos de idade. Métodos: Tratou-se de um estudo descritivo, realizado numa cidade do interior do estado do Paraná, nos anos de 2007 e 2008, em ambientes escolar e domiciliar. Doze crianças, de ambos os gêneros, participaram do estudo, com idade variando entre 5 anos e 2 meses e 6 anos completos, além de suas mães e respectivos professores. Entrevistas foram feitas com as mães e aplicação de questionário com os professores. Em seguida, observações da comunicação das crianças nos ambientes escolar e domiciliar. A análise de dados contemplou aqueles relevantes sobre o desenvolvimento das crianças e o desempenho escolar, buscando traçar o perfil comunicativo destas nos ambientes escolar e domiciliar, a partir de protocolos indicadores de meios e funções comunicativas. Resultados: Os resultados indicaram a presença de uma criança com saúde geral debilitada, com intercorrências desde o período gestacional, atraso motor e linguístico e baixo desempenho escolar. Observou-se também que todas as crianças utilizaram o meio verbal para se comunicar e a frequência mais alta de funções comunicativas apareceu em ambiente domiciliar, indicando um importante aspecto a ser considerado na estimulação da comunicação dessas crianças. Conclusão: Os dados deste estudo permitiram concluir que as crianças beneficiaram-se mais de contextos planejados com interlocutores familiares.
Keywords: desenvolvimento infantil; linguagem infantil; educação infantil